Can plasma vitamin C predict survival in stage IV colorectal cancer patients? Results of a prospective cohort study - Temraz, Sally; Jabbour, Jana; Nassar, Farah; El Helou, Remie; Hadla, Ruba; Mezher, Maria; El Lakkiss, Ahmed; Charafeddine, Maya; Nasr, Rihab; Shamseddine, Ali (Frontiers in Nutrition, 2023)
Background & Aims: In light of the inconclusive evidence on the association between vitamin C status and colorectal cancer (CRC) outcome, this study assessed the prognostic value of vitamin C in participants with metastatic CRC (mCRC). Methods: Adults with mCRC and cancer-free controls were recruited in this prospective cohort study to allow for comparison of vitamin C levels with healthy individuals from the same population. Sociodemographic, lifestyle, medical variables, BRAF and KRAS mutations, as well as Vitamin C plasma level and food intake were evaluated. Predictors of diminished vitamin C level were assessed via multivariate logistic regression. Mortality and progression free survival (PFS) among mCRC participants were analyzed based on plasma vitamin C level. Results: The cancer group (n=46) was older (mean age: 60±14 vs. 42 ±9.6, P=0.047) and included more males (29% vs. 19%, P<0.001) than the cancer-free group (n=45). There was a non-significant difference in the vitamin C intake between the two groups; however, the mean plasma vitamin C level was lower in the cancer group (3.5 ±3.7 vs. 9.2± 5.6mg/L, P<0.001). After adjusting for age and gender, the cancer group was more likely to be deficient compared to the cancer-free group [Adjusted Odds Ratio (95%CI): 5.4 (2.1-14)]. There was a non-significant trend for higher mortality in the vitamin C deficient cancer group (31% vs 12%, P=0.139). PFS did not differ based on vitamin C deficiency and patients with BRAF and KRAS mutations did not have significant differences in vitamin C levels. Conclusion: mCRC patients have lower plasma vitamin C levels than healthy controls. The trend toward higher mortality in the vitamin C deficient cancer group was not statistically significant. Whether this phenomenon affects survival and response to treatment warrants further exploration in phase III clinical trials.